2019
DOI: 10.1002/eji.201948154
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33‐activated murine mast cells control the dichotomy between RORγt+ and Helios+Tregs via the MK2/3‐mediated IL‐6 production in vitro

Abstract: In mast cells, IL-33 typically induces the activation of NF-κB, which results in the production of cytokines such as IL-6 and IL-2. Here, we demonstrate that the IL-33-induced IL-6 production in murine mast cells and the formation of RORγt + T regs essentially depends on the MAPKAPs, MK2, and MK3 (MK2/3) downstream of MyD88. In contrast to this, the IL-33-induced and MyD88-dependent IL-2 production in mast cells contributes to the maintenance of Helios + T regs . Thereby, the IL-33-induced IL-2 response and, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 60 publications
2
29
0
Order By: Relevance
“…Interestingly, the addition of IL‐2 recovered the maintenance of RORγt − Helios + T regs in the presence of IL‐3 and IL‐33 (Figure 4A,B). This suggested that the reduction in RORγt − Helios + T regs resulted from a deficiency of IL‐2 in the culture, which is normally produced by IL‐33‐stimulated BMMCs 21 . In contrast to conditions with SCF costimulation, 21 IL‐3 strongly reduced the IL‐33‐induced production of IL‐2 by mast cells (Figure 4C).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Interestingly, the addition of IL‐2 recovered the maintenance of RORγt − Helios + T regs in the presence of IL‐3 and IL‐33 (Figure 4A,B). This suggested that the reduction in RORγt − Helios + T regs resulted from a deficiency of IL‐2 in the culture, which is normally produced by IL‐33‐stimulated BMMCs 21 . In contrast to conditions with SCF costimulation, 21 IL‐3 strongly reduced the IL‐33‐induced production of IL‐2 by mast cells (Figure 4C).…”
Section: Resultsmentioning
confidence: 97%
“…We recently showed that IL‐33‐stimulated BMMCs induce RORγt + T regs from RORγt − T regs 21 . We analysed Tregs in the cocultures with mast cells as represented by the gating strategy shown in Figure B.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2020) 10:8152 | https://doi.org/10.1038/s41598-020-65072-3 www.nature.com/scientificreports www.nature.com/scientificreports/ the p38-MK2/3 signaling module and JNK1/2. Similar to mast cells 12,31,36 the p38-MK2/3 signaling module limits the activation of JNK1/2 and thus the proliferation of BMDCs by feedback inhibition ( Supplementary Fig. 3A).…”
Section: Discussionmentioning
confidence: 99%